New self-organized task scheduling topology structure in p2p computing——K+tree - CHEN Hong-wei1; WANG Ru-chuan1 (Tongxin xuebao)
A new self-organized task scheduling topology structure—K+ tree—was provided. A K+ tree was composed of a L-tier K-ary tree and a （L?1）-tier K-ary tree. The basic function unit of a K+ tree was comprised of a coordinator peer, a backup coordinator peer, and K worker peers. Key technologies were expatiated on which include how a non-organized graph changes into a self-organized K+ tree, how a coordinator selects worker peers and a backup coordinator peer, and how a K+ tree realizes balancing load among peers. K+ tree had high reliability and scalability, and it can lower the average running time of tasks effectively in certain conditions via analysis and simulation.